Diseño de un plan de negocios a través de una consultora empresarial, como alternativa para contrarrestar la problemática del coronavirus, en la ciudad de Bogotá - Herrera Delgado, Denisse Tatiana (Universidad Antonio Nariño, 2021)
In the design of a business plan through a business consultancy, as an alternative to counteract the problem of the coronavirus in the city of Bogotá, teleworking is carried out under the approach of Colombian laws specifically 1221 of 2008 and decree 884 of 2012 that regulates it.